Alternative technologies for tomato post-harvest quality preservation - Pinheiro, Joaquina (2014)
Fresh tomato (Solanum lycopersicum) is one of the most consumed fruits and the preservation of itsquality and shelf-life extension is a continuous challenge. An understanding of fruit deteriorationfactors allows the investigation of new approaches to reach this objective. Fruit preservationis achieved by destroying enzymes and micro-organisms, and reducing physiological disorders,using treatments such as chlorinated water (HIPO), ozone, low or high temperatures, ultrasounds,UV-C radiation, modified atmosphere packaging, edible coatings and 1-methylcyclopropene. In thisreview, a description of action, advantages and disadvantages of each preservation treatment,and corresponding effects on tomato quality and safety are presented. The development of agreentechnology for tomato has advantages for all fresh chain interventions, with direct or indirectimpacts on human health.